A study of the roles of school administrators in increasing the quality of school life through social responsibility projects in primary schools - Doygunel, Aşkın; Koprulu, Fatma (Frontiers in Psychology, 2022)
The structure and expectations of societies are constantly changing, developing and advancing as time demands. Accordingly, the vision, mission, purpose and objectives of educational institutions are changing, and are shaped according to the expectations of the society. School Directors, teachers and families, briefly the community, should know that schools are institutions that best fulfil children's learning, make them feel happy and safe. A cheerful and peaceful school environment always brings academic success. Children who have a quality school life are aware of the responsibility for their behaviours as well as the social responsibilities for their environment. Thus, students who are closely interested in social responsibility projects are not just academically developed; at the same time, their social, emotional and mental development increases and their social cohesion and awareness develop. This research aims to examine ways to improve the quality of social life in schools through social responsibility projects to be started as well as opinions by school Directors. In this study, the Qualitative Method and Case Study Design were used. The study group of this research consisted of 15 teachers working in primary schools affiliated with the Department of Primary Education of the Ministry of National Education. The participants were interviewed through live connections.The findings revealed that students are very willing to take part in social responsibility projects, and significant improvements have been made in their academic achievement, they attended more willingly and there have been noticeable changes in the quality of the school.